Gender in the Post-Fordist Urban : The Gender Revolution in Planning and Public Policy - van den Berg, Marguerite (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book investigates the gender revolution in urban planning and public policy. Building on feminist urban studies, it introduces the concept of genderfication as a means of understanding the consequences of post-Fordist gender notions for the city. It traces the changes in western urban gender relations, arguing that in the post-Fordist urban landscape gender is used for urban planning and public policy - both to rebrand a city's image and to produce space for gender-equal ideals, often at the cost of precarious urban populations. This is a topic that remains largely unexplored in critical urban studies and radical geography. Chapters cover how Jane Jacobs' perspectives provide an alternative to the patriarchal modernist city for contemporary planners and using Rotterdam as a case study Van Den Berg discusses why new urban planning methods focus on attracting women and children as new urbanites. Topics include: forms of place marketing, gender as a repertoire for contemporary urban Imagineering and the concept of urban re-generation. The final chapter investigates how cities aiming to redefine themselves imagine future populations and how they design social policies that explicitly and particularly target women as mothers. Scholars in all fields of urban studies will find this work thought-provoking, instructive and informative.
Keywords: Social sciences.; Urban geography.; Urban planning.; City planning.; Sociology.; Sociology, Urban.; Human geography.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books